Real estate fintech : the instant buying business model and its applications in the hotels and resorts industry - Gargiulo, Vittorio (2023)
This study aims to analyse the instant buyer business model in the real estate fintech landscape and understand its potential application in the hospitality industry. In order to address this research question, we analysed the ibuyer model in the real estate industry, examining its main success factors and how they might translate to the hotel and resort industry. We also identified the main variables that influence hotel room prices and examined how much they explain hotel selling prices to determine whether automated valuation models (AVMs) can be used to accurately forecast revenues in this industry. In general, the results showed that hotel prices are conditioned not only by observable characteristics of the hotel facility but also by variables that have emerged only recently, such as online reviews on booking portals. Our findings suggest that the ibuyer business model has the potential to be successful in the hospitality industry as well, given that the developed models explain a high share of the variation in reselling prices. Our analysis suggests that AVMs can be a useful tool for hotel room valuation and pricing, although further research is needed to confirm their accuracy and applicability. This research contributes to the existing academic literature on PropTech and the instant buyer business model and has practical implications for managers operating in the hospitality industry, who now have more tools to correctly plan their sales strategy.